Osteology of Hyrcanian crested loach, Paracobitis hircanica (Pisces, Nemacheilidae) - Azimi, H.; Mousavi-Sabet, H.; Eagderi, S. (Our Nature, 2015)
This study was carried out to describe of osteological structure of the newly described crested loach, Paracobitis hircanica Mousavi-Sabet et al., 2015. For this purpose, ten specimens were collected from the Zaringol River, in the southeastern Caspian Sea basin. After clearing and staining, osteologicl characteristics were examined. The obtained results showed that the P. hircanica is osteologicaly characterized by plate-like protrusion in epibranchial-4, no sesamoid ossifications, five hypurals, free and long epural, no connection between retroarcticulare and dental, loss of preethmoideum-I and basibranciale-4, alveolar bony capsule and presence of the manubrium. Our Nature (2015), 13(1): 8-18